Pressureless sintering aluminum nitride ceramic and preparation method and application thereof

By introducing nano-grade molybdenum powder and fluoride sintering additives into aluminum nitride ceramics, and using pressure-free sintering process, the problem of aluminum nitride ceramics taking into account high thermal conductivity and high bending strength is solved, moderate resistivity and excellent mechanical properties are achieved, and dielectric layer materials are suitable for electrostatic chucks.

CN119638437APending Publication Date: 2025-03-18HUAZHONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202411972100.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When existing aluminum nitride ceramics take into account high thermal conductivity and high bending strength, it is difficult to meet the requirements of electrostatic chucks for resistivity, thermal conductivity and mechanical properties.

Method used

By introducing nano-grade molybdenum powder and fluoride sintering aid, the pressure-free sintering process is adopted to deoxygenate at low temperature and generate molybdate to form dense and highly thermally conductive aluminum nitride ceramics.

Benefits of technology

Aluminum nitride ceramics with high thermal conductivity and high bending strength at lower sintering temperatures are achieved, and the resistivity is moderate, meeting the use needs of electrostatic chucks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638437A_ABST
    Figure CN119638437A_ABST
Patent Text Reader

Abstract

The invention discloses pressureless sintered aluminum nitride ceramic as well as a preparation method and application thereof. The preparation method comprises the following steps: ball-milling and mixing micron-sized aluminum nitride, a sintering aid, nano-sized molybdenum powder, a dispersing agent, a binder and an organic solvent to prepare slurry; and drying the slurry, granulating, forming, dumping and sintering to obtain the pressureless sintered aluminum nitride ceramic. Wherein the sintering aid is a combination of samarium fluoride and yttrium fluoride. According to the preparation method, oxygen is removed at a low temperature by virtue of strong affinity of the nanoscale molybdenum powder and oxygen, the nanoscale molybdenum powder and the sintering aid jointly play a role in liquid-phase sintering assistance at a high temperature, densified sintering is realized and grain growth is inhibited by adopting pressureless sintering at a relatively low sintering temperature, the aluminum nitride ceramic with both heat conduction and strength is obtained, and meanwhile, a low-resistance second phase is generated; the resistivity of the aluminum nitride ceramic is adjusted while the heat conduction characteristic of the aluminum nitride ceramic is improved, the electrical conductivity of the aluminum nitride material is improved, and finally the aluminum nitride ceramic with high heat conduction and bending strength and moderate resistivity is obtained to meet the use requirements of electrostatic chucks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum nitride ceramics, and in particular to a pressureless sintered aluminum nitride ceramic and a preparation method and application thereof. Background Art

[0002] Aluminum nitride (AlN) ceramics have the characteristics of high thermal conductivity and low thermal expansion coefficient. They can be used as ideal heat dissipation and packaging materials for large-scale integrated circuits, high-power devices, etc. In addition, by adjusting its resistance value, it can also be used as microwave attenuation materials, electrostatic chuck dielectric layer materials, etc. It has broad applications in high-power microwave electronic vacuum devices and semiconductor devices. Electrostatic chuck is a device that uses electrostatic adsorption force to clamp the wafer. It is widely used in semiconductor equipment such as CVD and PVD. The dielectric layer in the electrostatic chuck needs to have appropriate conductive properties (volume resistivity is 10 9 ~10 11 Ω·cm), excellent thermal conductivity and high flexural strength. Aluminum nitride is a covalent compound with a small self-diffusion coefficient and is difficult to react chemically with other substances. It usually requires a higher sintering temperature to achieve densification. At the same time, the presence of oxygen impurities in aluminum nitride powder will form aluminum vacancies, form phonon-defect scattering, and deteriorate thermal conductivity. Therefore, high temperature is required to migrate oxygen impurities to the grain boundaries to obtain high thermal conductivity. Usually, the temperature of pressureless sintering is above 1800℃, or hot pressing sintering is required to obtain dense and highly thermally conductive ceramics, which has high requirements on equipment and causes high energy consumption. The introduction of sintering aids can promote the densification of aluminum nitride ceramics and remove lattice oxygen in aluminum nitride, thereby improving the thermal conductivity of the material, but it will also reduce the flexural strength of the ceramics, making the reliability of aluminum nitride reduced. Therefore, aluminum nitride ceramics have the problem that it is difficult to simultaneously take into account high thermal conductivity and high flexural strength.

[0003] Adding reinforcing phases can be used to improve the mechanical properties of ceramics. However, the thermal conductivity of most ceramic materials is much lower than that of aluminum nitride. Although the introduction of these substances can improve the mechanical strength of the material, it will lead to a sharp decrease in the thermal conductivity of aluminum nitride ceramics. Si3N4 whiskers have a high aspect ratio, thermal conductivity, fracture strength, elastic modulus and low thermal expansion coefficient, which can match the physical and chemical properties of the aluminum nitride matrix well. With the help of whisker bridging, pull-out and crack deflection, the bending strength of aluminum nitride ceramics can be improved. For example, patent CN112745126 A (a Si3N4 whisker-toughened high thermal conductivity AlN ceramic substrate and preparation method) and patent CN 115286409 A (a silicon nitride whisker-reinforced aluminum nitride composite ceramic material and its preparation method) are based on this technical route, which effectively improves the bending strength of aluminum nitride ceramics. However, due to the orientation of the whiskers, it is difficult to ensure uniform distribution in the ceramic body, and the whiskers will inevitably be damaged and broken during the ball milling process. In addition, Si3N4 has excellent insulation properties and cannot reduce the resistivity of aluminum nitride ceramics. Due to the high insulation of aluminum nitride, the application of electrostatic chucks requires the addition of a certain amount of low-resistance materials to reduce the resistivity of aluminum nitride ceramics, such as metals, carbon materials, and TiN. The thermal conductivity of materials such as TiN is much lower than that of aluminum nitride, which will cause a significant reduction in the thermal conductivity of ceramics; the high melting point characteristics of metals and carbon materials will reduce the density of aluminum nitride ceramics and will also have an adverse effect on thermal conductivity. Some researchers have proposed the introduction of graphene to adjust the resistance and obtain aluminum nitride ceramics with high thermal conductivity. However, the introduction of carbon materials will make it difficult to densify aluminum nitride, and higher sintering temperatures or hot pressing sintering are required to achieve densification. Patent CN 116813352 A uses a mixture of micron-sized aluminum nitride powder, single-layer graphene and sintering aids to prepare a product with a relative density of more than 98.8% and a volume resistivity of 10 9 ~10 11Ω·cm, aluminum nitride ceramics with thermal conductivity exceeding 200W·m, but its sintering temperature is above 1700℃, and the requirement for oxygen impurity content in aluminum nitride powder is high (≤0.3%). However, the oxygen content of aluminum nitride powder commonly used in business is mostly around 1wt% (0.8%-1.2%). Therefore, using existing commercial aluminum nitride powder, balancing high strength and high thermal conductivity is also a problem to be solved by aluminum nitride ceramics. Hot pressing sintering can reduce the sintering temperature and effectively inhibit grain growth, thereby obtaining dense and high-strength AlN ceramics, but hot pressing sintering has high requirements for molds and equipment. At the same time, the second phase produced during sintering is difficult to precipitate, which has an adverse effect on thermal conductivity. Patent CN 112811909 A (a method for preparing high-strength and high-thermal conductivity aluminum nitride by hot pressing sintering, using a method combining pre-sintering-hot pressing sintering-high temperature annealing) effectively improves the thermal conductivity of hot pressed sintered aluminum nitride ceramics. However, the sintering system of this method includes pre-sintering at 1400~1600℃, hot pressing sintering at 1650~1800℃ (pressure reaches 15~45 MPa) and high-temperature annealing at 1750~1800℃, and the process is relatively complicated.

[0004] Therefore, there is an urgent need to provide a low-cost aluminum nitride ceramic material with high thermal conductivity and bending strength suitable for electrostatic chucks and a preparation method to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to overcome the above technical deficiencies, propose a pressureless sintered aluminum nitride ceramic and its preparation method and application, solve the problem that the high thermal conductivity and bending strength of aluminum nitride ceramics in the prior art are mutually restricted, and the moderate resistivity (10 9 ~10 11 It is difficult to balance high resistivity (Ω·cm) and high thermal conductivity, and it is difficult to meet the technical requirements of electrostatic chuck dielectric materials on resistivity, thermal conductivity and mechanical properties.

[0006] In a first aspect, the present invention provides a method for preparing a pressureless sintered aluminum nitride ceramic, comprising the following steps: The micron-sized aluminum nitride, sintering aid, nano-sized molybdenum powder, dispersant, binder and organic solvent are ball-milled and mixed to obtain a slurry; The slurry is dried and granulated to obtain granulated powder; forming the granulated powder to obtain a green body; Debinding the green body to obtain a debinded green body; The debinding green body is sintered to obtain pressureless sintered aluminum nitride ceramics; wherein, The sintering aid is a combination of samarium fluoride and yttrium fluoride.

[0007] In a second aspect, the present invention provides a pressureless sintered aluminum nitride ceramic, which is obtained by the preparation method of the pressureless sintered aluminum nitride ceramic provided by the first aspect of the present invention.

[0008] In a third aspect, the present invention provides the use of the pressureless sintered aluminum nitride ceramic as a dielectric layer material for an electrostatic chuck.

[0009] Compared with the prior art, the beneficial effects of the present invention include: The present invention utilizes the strong affinity of nano-scale molybdenum powder with oxygen, which can play a role of deoxidation at low temperature, and plays a role of liquid phase sintering aid together with the composite sintering aid at high temperature, and adopts pressureless sintering at a relatively low sintering temperature to achieve densification sintering and inhibit grain growth, thereby obtaining aluminum nitride ceramics that take into account both thermal conductivity and strength. At the same time, the reaction with the sintering aid generates a low-resistance second phase, which improves the thermal conductivity of the aluminum nitride ceramic while adjusting its resistivity, improving the electrical conductivity of the aluminum nitride material, and finally obtaining aluminum nitride ceramics with high thermal conductivity, bending strength and moderate resistivity to meet the use requirements of the electrostatic chuck. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 is a SEM image of the aluminum nitride ceramic prepared in Example 1 of the present invention; Figure 2 is the EDS element distribution diagram of Mo in the aluminum nitride ceramic prepared in Example 4 of the present invention; Figure 3 is the XRD pattern of the aluminum nitride ceramic prepared in Example 1 of the present invention; Figure 4 It is the XRD diagram of the aluminum nitride ceramic prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0012] During the storage process, aluminum nitride powder will inevitably absorb oxygen in the environment, increasing its oxygen content. On the one hand, oxygen will replace nitrogen to form aluminum vacancy defects, increasing phonon scattering; on the other hand, it will react with sintering aids during sintering to form a second phase with low thermal conductivity and enrich, thereby deteriorating the thermal conductivity of aluminum nitride ceramics. The thermal conductivity of aluminum nitride is related to the lattice oxygen and second phase in aluminum nitride. In order to obtain high thermal conductivity, it is necessary to reduce the second phase with poor thermal conductivity and the lattice oxygen content, which means that it is necessary to keep the heat at high temperature for a long time or use aluminum nitride powder with very low oxygen content. However, high temperature and long-term heat preservation will increase the grain size and have an adverse effect on the bending strength of the ceramic. Metal molybdenum has a high melting point (2610℃), high thermal conductivity (138 W / m·K), excellent mechanical properties, a thermal expansion coefficient similar to that of aluminum nitride, and good dispersibility and compatibility. It can be a potential reinforcement phase for improving the bending strength of aluminum nitride ceramics and adjusting the resistivity of the material. At the same time, since metal molybdenum powder is easily oxidized, it can act as a deoxidizer in AlN, thereby improving its thermal conductivity. However, its high melting point will cause the density of aluminum nitride / molybdenum composite materials to decrease with the increase of Mo addition, thereby deteriorating the thermal conductivity of the material.

[0013] The present invention introduces nano molybdenum powder with high thermal conductivity, good toughness and thermal expansion coefficient matching AlN, which can react with oxygen adsorbed in the green body at low temperature to remove oxygen impurities in aluminum nitride; and generates molybdate with pyrochlore structure in situ with fluoride during sintering, avoiding premature volatilization of fluoride sintering aid, and the formed molybdate is pinned at the three-pronged grain boundary of AlN, and the dispersed molybdate inhibits grain growth while improving the direct contact between aluminum nitride grains, and by means of crack deflection, can simultaneously improve the thermal conductivity and mechanical properties of AlN ceramics. The present invention adopts samarium fluoride and yttrium fluoride as composite sintering aids, reducing the oxygen impurities additionally introduced by oxide sintering aids; the melting points of samarium fluoride and yttrium fluoride are 1306℃ and 1387℃ respectively, and liquid phase can be formed at a relatively low temperature, which plays the role of infiltrating aluminum nitride powder to promote powder particle rearrangement and reduce sintering temperature. The present invention reduces the insulation resistance of aluminum nitride ceramics by regulating the content of metal molybdenum and optimizing a suitable sintering aid, thereby generating a low-resistance phase and obtaining a ceramic material with a moderate resistivity.

[0014] Based on this, the present invention is proposed.

[0015] In a first aspect, the present invention provides a method for preparing a pressureless sintered aluminum nitride ceramic, comprising the following steps: S1. Mixing: ball-milling micron-sized aluminum nitride, sintering aid, nano-sized molybdenum powder, dispersant, binder and organic solvent to obtain a slurry; wherein the sintering aid is a combination of samarium fluoride and yttrium fluoride; S2, granulation: drying the slurry and granulating it to obtain granulated powder; S3, molding: molding the granulated powder to obtain a green body; S4, debinding: debinding the green body to obtain a debinded green body; S5. Sintering: Sintering the debinding green body to obtain AlN ceramics.

[0016] In this embodiment, in step S1, the average particle size of the micron-sized aluminum nitride is 1.0-2.0 μm.

[0017] In this embodiment, in step S1, the oxygen content of the micron-sized aluminum nitride is ≤1.2wt%, preferably 0.8-1.2wt%.

[0018] In this embodiment, in step S1, the mass ratio of samarium fluoride to yttrium fluoride is 1:(0.6-1.5). The present invention can effectively promote the densification sintering of aluminum nitride ceramics by controlling the mass ratio of samarium fluoride to yttrium fluoride within this range, and obtain aluminum nitride ceramics with high thermal conductivity under pressureless sintering conditions; if the proportion of samarium fluoride is too high, the second phase is mainly samarium aluminate; if the proportion of samarium fluoride is too low, the second phase is mainly yttrium aluminate, so that the aluminum nitride ceramic has good insulation properties, and it is difficult to obtain aluminum nitride ceramics with moderate resistivity.

[0019] In this embodiment, in step S1, the average particle size of the sintering aid is 1.0-2.0 μm.

[0020] In this embodiment, in step S1, the mass ratio of micron-sized aluminum nitride to sintering aid is 1: (0.03-0.06). The present invention can obtain dense and highly thermally conductive aluminum nitride ceramics under pressureless sintering conditions by controlling the mass ratio of micron-sized aluminum nitride to sintering aid within this range. If the amount of sintering aid added is too low, aluminum nitride is difficult to densify under pressureless sintering conditions; if the amount of sintering aid added is too high, although the densification sintering of aluminum nitride ceramics can be achieved, too much second phase is formed and aggregated at the grain boundary, and the thermal conductivity is reduced.

[0021] In this embodiment, in step S1, the average particle size of the nano-scale molybdenum powder is 10-100 nm, and further is 40 nm.

[0022] In this embodiment, in step S1, the mass ratio of micron-grade aluminum nitride to nano-grade molybdenum powder is 1: (0.005-0.02). The present invention can obtain aluminum nitride ceramics with high thermal conductivity, bending strength and moderate resistivity by controlling the mass ratio of micron-grade aluminum nitride to nano-grade molybdenum powder within the above range. If the amount of nano-grade molybdenum powder added is too low, the resistivity is limited and the thermal conductivity and bending strength are not improved much, which cannot meet the application requirements of the electrostatic chuck; if the amount of nano-grade molybdenum powder added is too high, the thermal conductivity and bending strength are reduced, and the resistivity is increased.

[0023] In this embodiment, in step S1, the dispersant is at least one of AKM0531 and Solsperse41000.

[0024] In this embodiment, in step S1, the dispersant accounts for 0.5%-1.1% of the total mass of the micron-grade aluminum nitride, the sintering aid, and the nano-grade molybdenum powder.

[0025] In this embodiment, in step S1, the binder is an ethanol solution of polyvinyl butyral with a concentration of 5%-10%.

[0026] In this embodiment, in step S1, the binder accounts for 5%-10% of the total mass of the micron-grade aluminum nitride, the sintering aid, and the nano-grade molybdenum powder.

[0027] In this embodiment, in step S1, the organic solvent is ethanol.

[0028] In this embodiment, in step S1, the mass ratio of the total mass of micron-sized aluminum nitride, sintering aid, and nano-sized molybdenum powder to the organic solvent is (1.2-1.5):1.

[0029] In this embodiment, in step S1, the ball milling time is 5-10 hours, the ball milling speed is 300-400 rpm, and the ball milling medium is zirconia balls.

[0030] In this embodiment, in step S2, granulation is performed by grinding and screening.

[0031] Preferably, the mesh size of the sieve is 50-100 meshes, further 80 meshes.

[0032] In this embodiment, in step S3, the molding process includes: sequentially performing dry pressing and cold isostatic pressing on the granulated powder.

[0033] Preferably, during the dry pressing process, the pressure is 2-5 MPa. The present invention realizes the preforming of the blank by dry pressing.

[0034] Preferably, during the cold isostatic pressing process, the pressure is 180-200 MPa. The present invention improves the density of the green body through cold isostatic pressing.

[0035] In this embodiment, in step S3, during the debinding process, the debinding temperature is 500-600°C, the holding time is 2-4 hours, the heating rate is 30-120°C / h, and the debinding atmosphere is a mixed atmosphere of protective atmosphere and H2.

[0036] Preferably, in the mixed atmosphere of protective atmosphere and H2, the volume content of H2 is 1%-5%.

[0037] In this embodiment, in step S4, during the sintering process, the highest sintering temperature is 1600-1700°C, the holding time of the highest sintering temperature is 1-10h, the heating rate is 2°C-10°C / min, and the sintering atmosphere is a protective atmosphere.

[0038] The present invention does not limit the type of protective atmosphere, and those skilled in the art can select it according to actual conditions. For example, the protective atmosphere can be nitrogen, argon, etc.

[0039] In a second aspect, the present invention provides a pressureless sintered aluminum nitride ceramic, which is obtained by the preparation method of the pressureless sintered aluminum nitride ceramic provided by the first aspect of the present invention.

[0040] In a third aspect, the present invention provides the use of the pressureless sintered aluminum nitride ceramic as a dielectric layer material for an electrostatic chuck.

[0041] Example 1 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 1.6g samarium fluoride (average particle size 1.8μm), 2.4g yttrium fluoride (average particle size 1.5μm), 0.4g nano molybdenum powder (average particle size 40nm), 0.422g dispersant AKM0531, 4.22g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1650°C at a rate of 5°C / min under flowing nitrogen conditions and kept for 6 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0042] Example 2 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 0.96g samarium fluoride (average particle size 1.8μm), 1.44g yttrium fluoride (average particle size 1.5μm), 0.4g nano molybdenum powder (average particle size 40nm), 0.414g dispersant AKM0531, 4.14g polyvinyl butyral ethanol solution (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1700°C at a rate of 10°C / min under flowing nitrogen conditions and kept for 3 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0043] Example 3 80g aluminum nitride powder (average particle size 1.2μm, oxygen content 1.0wt%), 2.4g samarium fluoride (average particle size 1.8μm), 1.6g yttrium fluoride (average particle size 1.5μm), 0.8g nano molybdenum powder (average particle size 40nm), 0.848g dispersant AKM0531, 4.24g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1600°C at a rate of 10°C / min under flowing nitrogen conditions and kept for 10 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0044] Example 4 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 1.92g samarium fluoride (average particle size 1.8μm), 2.88g yttrium fluoride (average particle size 1.5μm), 1.6g nano molybdenum powder (average particle size 40nm), 0.87g dispersant AKM0531, 4.36g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, kept at this temperature for 3 hours, and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible, heated to 1700°C at a rate of 5°C / min under flowing nitrogen conditions, kept at this temperature for 1 hour, and then cooled to 1550°C at a rate of 5°C / min and kept at this temperature for 5 hours, and the surface was polished to obtain aluminum nitride ceramics.

[0045] Comparative Example 1 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 1.6g samarium fluoride (average particle size 1.8μm), 2.4g yttrium fluoride (average particle size 1.5μm), 0.42g dispersant AKM0531, 4.2g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1650°C at a rate of 5°C / min under flowing nitrogen conditions and kept for 6 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0046] Comparative Example 2 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 1.6g samarium fluoride (average particle size 1.8μm), 2.4g yttrium fluoride (average particle size 1.5μm), 0.4g nano molybdenum powder (average particle size 40nm), 0.422g dispersant AKM0531, 4.22g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace, debinded in an air atmosphere, heated to 550°C at a rate of 60°C / h, kept at that temperature for 3 hours, and then cooled in the furnace. The debinded green body was placed in a boron nitride crucible, heated to 1650°C at a rate of 5°C / min under flowing nitrogen conditions, and kept at that temperature for 6 hours. The surface was polished to obtain aluminum nitride ceramics.

[0047] Comparative Example 3 80g aluminum nitride powder (average particle size 1.2μm, oxygen content 1.0wt%), 2.4g samarium fluoride (average particle size 1.8μm), 1.6g yttrium fluoride (average particle size 1.5μm), 0.8g micron-grade molybdenum powder (average particle size 2μm), 0.848g dispersant AKM0531, 4.24g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1600°C at a rate of 10°C / min under flowing nitrogen conditions and kept for 10 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0048] Comparative Example 4 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 4.0g yttrium fluoride (average particle size 1.5μm), 0.4g nano molybdenum powder (average particle size 40nm), 0.422g dispersant AKM0531, 4.22g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1650°C at a rate of 5°C / min under flowing nitrogen conditions and kept for 6 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0049] Comparative Example 5 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 4.0g samarium fluoride (average particle size 1.8μm), 0.4g nano molybdenum powder (average particle size 40nm), 0.422g dispersant AKM0531, 4.22g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1650°C at a rate of 5°C / min under flowing nitrogen conditions and kept for 6 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0050] Comparative Example 6 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 1.6g samarium fluoride (average particle size 1.8μm), 2.4g yttrium fluoride (average particle size 1.5μm), 3.2g nano molybdenum powder (average particle size 40nm), 0.436g dispersant AKM0531, 4.36g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1650°C at a rate of 5°C / min under flowing nitrogen conditions and kept for 6 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0051] Comparative Example 7 80g aluminum nitride powder (average particle size 1.68μm, oxygen content 0.8wt%), 1.6g samarium fluoride (average particle size 1.8μm), 2.4g yttrium fluoride (average particle size 1.5μm), 0.4g nano molybdenum powder (average particle size 40nm), 0.422g dispersant AKM0531, 4.22g ethanol solution of polyvinyl butyral (concentration 5wt%) and 60g alcohol were put into a ball mill for 6h, the speed was 365 rpm, and the ball milling medium was zirconium oxide ball. The obtained slurry was dried in an oven at 70℃, and after grinding, it was passed through an 80-mesh sieve to obtain granulated powder. The granulated powder was loaded into a mold and the powder was compacted by a hydraulic press at 3MPa, and then the pre-pressed green body was subjected to cold isostatic pressing at 200MPa to obtain a green body. The green body was placed in a tube furnace for debinding, and a nitrogen mixture containing 1 vol% hydrogen was passed through water and then introduced into the tube furnace, and the temperature was raised to 550°C at a rate of 60°C / h, and the temperature was kept for 3 hours and then cooled with the furnace. The green body after debinding was placed in a boron nitride crucible and heated to 1750°C at a rate of 10°C / min under flowing nitrogen conditions and kept for 3 hours. The aluminum nitride ceramic was obtained after the surface was polished.

[0052] Performance Testing The performance of the aluminum nitride ceramics prepared in the above examples and comparative examples was tested. The test results are shown in Tables 1 and Figure 1-4 .in, Density: The ratio of the actual density of ceramics to the theoretical density of ceramics. The actual density of ceramics is tested by the Archimedes method, and the theoretical density of ceramics is calculated based on the composition.

[0053] Thermal conductivity: The laser flash point method was used to test the thermal diffusivity of the ceramic sample at room temperature using a laser thermal conductivity meter and the thermal conductivity was calculated.

[0054] Bending strength: The bending strength of ceramics was tested at room temperature using a universal material testing machine using a three-point bending method, with a measuring span of 30 mm.

[0055] Volume resistivity: Use an insulation resistance tester to test the volume resistivity of aluminum nitride ceramics at room temperature.

[0056] Table 1

[0057] Please refer to Table 1. It can be seen from Table 1 that the relative density of the aluminum nitride ceramics obtained in the embodiments of the present invention is greater than 99%, and the resistivity is within 10 9 ~10 11 Ω·cm, the thermal conductivity is greater than 200W / m·K, and the mechanical properties are significantly improved, reaching above 300MPa.

[0058] Compared with Example 1, in Comparative Example 1, no nano-molybdenum powder was added, and the thermal conductivity and bending strength of the aluminum nitride ceramics were significantly reduced, and the volume resistivity was significantly increased, indicating that the nano-molybdenum powder can not only reduce the resistivity of the aluminum nitride ceramics, but also effectively improve its bending strength and thermal conductivity.

[0059] Compared with Example 1, the debinding atmosphere in Comparative Example 2 is air, and the thermal conductivity, bending strength and volume resistivity of the aluminum nitride ceramic are significantly reduced, indicating that nitrogen-hydrogen as a debinding atmosphere can effectively prevent the oxidation of molybdenum powder, so that it plays a good deoxidation role during sintering, thereby improving the thermal conductivity and bending strength of the ceramic, but it will cause the volume resistivity to increase, but it is still enough to meet the needs of the electrostatic chuck.

[0060] Compared with Example 3, in Comparative Example 3, micron-grade molybdenum powder is used, and the thermal conductivity and bending strength of the aluminum nitride ceramic are significantly reduced, and the volume resistivity is significantly increased, indicating that compared with micron-grade molybdenum powder, nano-molybdenum powder has a larger specific surface area and better dispersibility, and can play a more effective deoxidation and enhancement role, which can not only improve the thermal conductivity and bending strength of the ceramic, but also reduce the volume resistivity.

[0061] Compared with Example 1, in Comparative Example 4, the sintering aid is a single yttrium fluoride, and the thermal conductivity and bending strength of the aluminum nitride ceramic are significantly reduced, and the volume resistivity is significantly increased, indicating that the samarium molybdate formed by the joint action of nano-scale molybdenum powder and the sintering aid in the present invention has the effect of reducing resistance, and the second phase has poor wettability with AlN, and is more likely to precipitate to the surface of the material along the grain boundaries. The residue is also mainly distributed at the triple grain boundaries, which increases the direct contact between the aluminum nitride grains and is beneficial to improving the thermal conductivity.

[0062] Compared with Example 1, in Comparative Example 5, the sintering aid is a single samarium fluoride, the thermal conductivity and bending strength of the aluminum nitride ceramic are significantly reduced, and the volume resistivity is significantly increased, and the second phase is mainly samarium aluminate, indicating that the composite sintering aid can effectively deoxidize and promote the formation of molybdate, thereby improving the thermal conductivity and bending strength of the ceramic and reducing the volume resistivity.

[0063] Compared with Example 1, in Comparative Example 6, an excessive amount of nano-molybdenum powder was added, and the thermal conductivity and bending strength of the aluminum nitride ceramic were significantly decreased, and the volume resistivity was slightly increased, indicating that the amount of nano-molybdenum powder added was too much, and the density decreased with the increase of the amount of nano-molybdenum powder added. The formation of pores further deteriorated the thermal conductivity and bending strength of the material, but the resistivity did not decrease with the increase of Mo, but instead increased.

[0064] Compared with Example 1, the sintering temperature in Comparative Example 7 is too high, and the thermal conductivity of the aluminum nitride ceramic increases, but the bending strength decreases significantly and the volume resistivity also increases significantly, indicating that the sintering temperature is too high. Although the impurity phase will precipitate out of the ceramic body and increase the thermal conductivity, it will lead to a significant decrease in bending strength and an increase in resistivity.

[0065] See also Figure 1 ,pass Figure 1 It can be seen that the aluminum nitride ceramic prepared in Example 1 of the present invention has a dense structure, the aluminum nitride grains are in close contact, and the second phase is evenly distributed at the triple grain boundary, which is beneficial to heat transmission.

[0066] See also Figure 2 ,pass Figure 2 It can be seen that the molybdate in the aluminum nitride ceramic prepared in Example 4 of the present invention is pinned at the triple crystal boundary, playing a reinforcing role.

[0067] See also Figure 3-4 ,pass Figure 3-4 It can be seen that the crystalline phase composition of the aluminum nitride ceramic prepared in Example 1 of the present invention includes AlN, YAM, and Sm2Mo2O7, while the crystalline phase composition of the aluminum nitride ceramic prepared in Comparative Example 1 of the present invention includes AlN, YAM, (Sm 0.5 Y 1.5 ) O3, it can be seen that the formation of trace rare earth molybdate in the present invention plays a role in regulating resistance, and the content of impurity phase in Example 1 is significantly lower than that in Comparative Example 1.

[0068] In summary, the present invention drives out oxygen at low temperature and generates isolated distributed toughening particles in situ, and controls the resistivity of aluminum nitride through reasonable composition and process design. The sintered ceramic has excellent thermal conductivity and strength and moderate resistivity, and there is no need to add whiskers to improve the bending strength of high thermal conductivity aluminum nitride ceramics. The present invention can directly use commercially available aluminum nitride powder with an oxygen content of about 1wt% based on a common pressureless sintering process and a sintering temperature below 1700°C, which has the characteristics of simple process, convenient operation and low cost.

[0069] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing pressureless sintered aluminum nitride ceramics, characterized in that: The following steps are involved: The micron-sized aluminum nitride, sintering aid, nano-sized molybdenum powder, dispersant, binder and organic solvent are ball-milled and mixed to obtain a slurry; The slurry is dried and then granulated to obtain granulated powder; Molding the granulated powder to obtain a green body; Debinding the green body to obtain a debinded green body; The debinding green body is sintered to obtain pressureless sintered aluminum nitride ceramics; wherein, The sintering aid is a combination of samarium fluoride and yttrium fluoride.

2. The method for preparing pressureless sintered aluminum nitride ceramics according to claim 1, characterized in that: The average particle size of the micron-sized aluminum nitride is 1.0-2.0 μm; and / or, The oxygen content of the micron-sized aluminum nitride is ≤1.2wt%.

3. The method for preparing pressureless sintered aluminum nitride ceramics according to claim 1, characterized in that: The mass ratio of samarium fluoride to yttrium fluoride is 1:(0.6-1.5); and / or, The average particle size of the sintering aid is 1.0-2.0 μm; and / or, The mass ratio of the micron-sized aluminum nitride to the sintering aid is 1:(0.03-0.06).

4. The method for preparing pressureless sintered aluminum nitride ceramics according to claim 1, characterized in that: The average particle size of the nano-scale molybdenum powder is 10-100 nm; and / or, The mass ratio of the micron-sized aluminum nitride to the nano-sized molybdenum powder is 1:(0.005-0.02).

5. The method for preparing pressureless sintered aluminum nitride ceramics according to claim 1, characterized in that: The dispersant is at least one of AKM0531 and Solsperse41000; and / or, The dispersant accounts for 0.5%-1.1% of the total mass of the micron-sized aluminum nitride, sintering aid, and nano-sized molybdenum powder; and / or, The binder is an ethanol solution of polyvinyl butyral with a concentration of 5%-10%; and / or, The binder accounts for 5%-10% of the total mass of the micron-grade aluminum nitride, sintering aid, and nano-grade molybdenum powder; The organic solvent is ethanol; and / or, The mass ratio of the total mass of the micron-sized aluminum nitride, the sintering aid, and the nano-sized molybdenum powder to the mass ratio of the organic solvent is (1.2-1.5):

1.

6. The method for preparing pressureless sintered aluminum nitride ceramics according to claim 1, characterized in that: During the ball milling mixing process, the ball milling time is 5-10 hours, the ball milling speed is 300-400 rpm, and the ball milling medium is zirconia balls; and / or, In the granulation process, the granulation is carried out by grinding and sieving, and the mesh number of the sieve is 50-100 meshes.

7. The method for preparing pressureless sintered aluminum nitride ceramics according to claim 1, characterized in that: The molding process includes: sequentially performing dry pressing and cold isostatic pressing on the granulated powder; wherein, During the dry pressing process, the pressure is 2-5 MPa; and / or, During the cold isostatic pressing process, the pressure is 180-200 MPa.

8. The method for preparing the pressureless sintered aluminum nitride ceramic according to claim 1, characterized in that: During the debinding process, the debinding temperature is 500-600°C, the holding time is 2-4 hours, the heating rate is 30-120°C / h, and the debinding atmosphere is a mixed atmosphere of protective atmosphere and H2; and / or, During the sintering process, the highest sintering temperature is 1600-1700° C., the holding time of the highest sintering temperature is 1-10 hours, the heating rate is 2° C.-10° C. / minute, and the sintering atmosphere is a protective atmosphere.

9. A pressureless sintered aluminum nitride ceramic, characterized in that: The pressureless sintered aluminum nitride ceramic is obtained by the preparation method of the pressureless sintered aluminum nitride ceramic according to any one of claims 1 to 8.

10. Use of the pressureless sintered aluminum nitride ceramic as claimed in claim 9 as a dielectric layer material for an electrostatic chuck.

Citation Information

Patent Citations

  • Si3N4 whisker toughened high-thermal-conductivity AlN ceramic substrate and preparation method thereof

    CN112745126A

  • Method for preparing high-strength and high-thermal-conductivity aluminum nitride through hot pressed sintering

    CN112811909A

  • Silicon nitride whisker reinforced aluminum nitride composite ceramic material and preparation method thereof

    CN115286409A

  • Aluminum nitride ceramic material as well as preparation method and application thereof

    CN116813352A

  • Aluminum nitride sintered body with high thermal conductivity and its preparation

    CA2171548A1

Cited By

  • High-thermal-conductivity ceramic material and additive manufacturing method thereof

    CN119661234A

  • Highly thermally conductive ceramic material and additive manufacturing method thereof

    CN119661234B

  • High-resistivity aluminum nitride ceramic substrate and preparation method thereof

    CN120483732A

  • A high-resistivity aluminum nitride ceramic substrate and preparation method thereof

    CN120483732B

  • Preparation method of high-strength aluminum nitride substrate

    CN121248301A